2010
DOI: 10.1590/s0104-12902010000600006
|View full text |Cite
|
Sign up to set email alerts
|

Interseccionalidade de gênero, classe e raça e vulnerabilidade de adolescentes negras às DST/aids

Abstract: Objetivo: verificar a vulnerabilidade ao HIV/aids de adolescentes femininas moradoras de favelas da cidade do Rio de Janeiro. Métodos: foi utilizada uma combinação de métodos, quantitativo e qualitativo. Na etapa quantitativa, realizou-se um estudo observacional de corte transversal por meio de entrevistas e exames clínico/laboratoriais para diagnóstico de DST, e, na qualitativa, desenvolveram-se grupos focais sobre os temas sexualidade, gênero e raça. Resultados: foram entrevistadas 816 adolescentes de 10 dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1
24

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 11 publications
0
10
1
24
Order By: Relevance
“…It is worth noting that black adolescents showed higher risk in the three indicators analyzed (physical violence, family violence, and bullying). A study with community-dwelling female adolescents in Rio de Janeiro found that the prevalence of being a victim or a perpetrator of violence was higher among those who considered themselves black 9 . The determinants of violence include macro determinants such as worst living conditions, exclusion in the process of urbanization, expansion of drug trafficking, and proximal determinants such as alcohol intake, other drugs use, and parental supervision 37,39 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that black adolescents showed higher risk in the three indicators analyzed (physical violence, family violence, and bullying). A study with community-dwelling female adolescents in Rio de Janeiro found that the prevalence of being a victim or a perpetrator of violence was higher among those who considered themselves black 9 . The determinants of violence include macro determinants such as worst living conditions, exclusion in the process of urbanization, expansion of drug trafficking, and proximal determinants such as alcohol intake, other drugs use, and parental supervision 37,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Although studies do not indicate this perspective, the hypothesis of this study findings is that black and indigenous populations live in vulnerable social realities that leads to greater exposure to risk factors for health such as drug use 41,42 . Racial discrimination experienced by women and men, black and white, occupies different places in social networks, providing different experiences 9 . For yellow adolescents, factors associated with a behavior of challenging parental limits in a more rigid family structure in terms of education are attributed as possible explanation for health vulnerabilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a whole, this suggests that physical intimate partner violence is also a socially determined health-disease process, a view supported by other Brazilian and international studies 1,7,34 . Thus, policies and programs to promote peace and deal with situations of violence (especially gender-related) should also tackle not only gender discrimination but also discrimination on grounds of color/ race and social class, since they are usually interrelated and superimposed 35,36 . They should thus include macrostructural actions that promote development and reduce social inequalities.…”
Section: Discussionmentioning
confidence: 99%
“…É sabido que a expansão das doenças sexualmente transmissíveis e o crescente número de gravidezes inoportunas na adolescência são problemas sociais que se relacionam diretamente com o estudo da sexualidade. Não são menos graves aqueles que sofrem sua influência indireta, embora marcante, como a violência de gênero e a violência relacionada às orientações sexuais (TAQUETTE, 2010;FENG et al, 2012).…”
unclassified